DEVELOPMENT OF NATIONALISM AND MULTICULTURALISM IN PAPUA THROUGH RELIGIOUS EDUCATION AT THE NURUL ANWAR KOMBA SENTANI ISLAMIC BOARDING SCHOOL - Rahman, Hendra Yulia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Papua, as a region with high cultural and ethnic diversity, faces significant challenges in building national unity and identity. This research focuses on the role of the Nurul Anwar Komba Sentani Islamic Boarding School in developing nationalism and multiculturalism in Papua through religious education. The research method uses a qualitative approach with in-depth interviews, observation and document analysis. The research results show that the Nurul Anwar Komba Sentani Islamic Boarding School not only conveys Islamic religious teachings, but also includes national values and love of the homeland in its religious education curriculum. Religious education at this Islamic boarding school emphasizes the understanding that Papua's cultural diversity is a wealth that must be protected, while unity and integrity are the foundation for the progress of this region as part of Indonesia. This Islamic boarding school is also active in organizing extracurricular activities that strengthen the sense of unity and integrity. Involving students in social and humanitarian activities, the Nurul Anwar Komba Sentani Islamic Boarding School makes a significant contribution to the formation of nationalist and multiculturalist character among the young generation of Papua. This research concludes that the role of the Nurul Anwar Komba Sentani Islamic Boarding School in developing nationalism and multiculturalism in Papua through religious education has a positive impact in overcoming challenges and strengthening a sense of national identity amidst Papua's cultural diversity. Religious education at this Islamic boarding school encourages the formation of a generation of Papuans who are not only religious but also have a nationalist and multiculturalist consciousness, ready to contribute to the progress of the Indonesian nation.